The Health Impacts of Extreme Weather Events in Africa: A scoping review protocol v1 - (:unkn) unknown (My University, 2023)
Background In the last 20 years, 12,000 extreme weather events worldwide led to devastating disasters, such as storms, floods, and heatwaves killing 500,000 people between 1999 and 2018. There is an imperative call for a deeper investigation of the intersection between weather extremes and health, especially in economically vulnerable countries that suffer the most. However, there are very few literature reviews on this research topic in low-income populations and even fewer in Africa. The existing review studies focus either on one particular weather hazard like floods or address specific aspects of human health or health systems. To our knowledge, our study is the first scoping review seeking to map the link between a wide range of health impacts (related to both physical and mental health) and extreme weather events. Our goal is to understand better the current and potential future outcomes of high-impact weather extremes on population health in Africa to support weather warnings and emergency decision-making toward a better capacity to prepare for and to cope with health risks. Methods The protocol is developed based on the PRISMA-P 2015 checklist for protocols (Moher et al., 2015). Recommended items for systematic review protocols are adapted to meet the objectives of our scoping review protocol. A scoping review (ScR) approach was chosen due to the broad nature of our research question. We will use established ScR methods to extract knowledge from studies on extreme weather events and the associated outcomes on the health of the populations in Africa. The study is designed according to the PRISMA extension for Scoping Reviews (PRISMA-ScR) (Tricco et al., 2018, Page et al., 2021). A comprehensive literature research will be conducted in four scientific databases: PubMed, Web of Science Core Collection, ScienceDirect, and EBSCOhost (Academic Search Complete, APA PsycArticle, APA PsycInfo, EncoLit, GeoRef, GeoRef in Process, Psycology and Behavioral
Keywords: African Research